Call me Mrs. Miracle [videorecording (DVD)] - Scott, Michael M.; Macomber, Debbie; Roberts, Doris, 1925-2016; Staite, Jewel; Johnson, Eric, 1979-; Holly, Lauren (Sony Pictures Home Entertainment, 2011)
This Christmas, Emily Merkle (aka Mrs. Miracle) is working in the toy department at Finley's. Her boss is Jake Finley, the owner's son, who needs a miracle to keep the business afloat. Holly Larson needs a miracle, too. Her widowed brother who is in the army won't be home for the holidays. For Christmas her nephew wants the toy robot he saw at Finley's, and she plans to get it for him. Fortunately, it's Mrs. Miracle to the rescue. Next to making children happy, she enjoys a bit of matchmaking.